Traditional healing practice in Rajbanshi and Satar Community of Jhapa, Nepal - Raut, B.; Khanal, D.P.; Kharel, A. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Jhapa is the easternmost district of Nepal and lies in Terai plains. Traditional healing system in Nepal has strong cultural and religious background. It exists in different ways such as ethnic or tribal group, ritual or ceremonial practices. In Nepal, traditional healers believe that the disease causing factors are not only the germ theory related but also the spiritual belief. As the census of 2011, there are eight densely populated indigenous ethnic communities including Satar and Rajbansi in Jhapa. The traditional healers of these communities with their indigenous knowledge serve the local people since time immemorial. The main objective of this research work was to find the traditional healing practice in Rajbanshi and Satar community of Jhapa, district, Nepal. Methods: The areas were visited from June 2017 to September 2017. A cross sectional study was performed to collect the information through semi structured questionnaires and face to face interviews with the traditional healers of Satar and Rajbanshi community. All together 20 locally reputed traditional healers, 10 from each community were selected. Results: Spiritual based five healing techniques and/or approaches, Phukphak, Tantrik Puja, Bali, Jantar-mantar and kul bigreko, used by traditional healers were explored. Moreover, 41 plant species belonged to 29 families were found to be used for the treatment of 22 common illnesses. 6 different dosage forms were used to prepare 28 traditional formulations. Conclusion: Spiritual based five healing techniques and/or approaches were used by traditional healers on this locality. We also identified different medicinal plant species that were used in different traditional formulation used by such healers. JMMIHS.2018;4(1):103-116